Dynamique spatiale et usage des schorres de l’Anse de l’Aiguillon de 1705 à nos jours. Enjeux de conservation d’un patrimoine naturel littoral marin - Laurent Godet; Laurent Pourinet; Emmanuel Joyeux; Fernand Verger (Cybergeo)
Coastal habitats have been deeply impacted and fragmented by human activities. In Europe, such habitats also benefit from rich and diverse historical archives (maps and writings) that allow accurate assessment of their spatial dynamics and the way they have been exploited by humans. Through the example of the saltmarshes of the Anse de l’Aiguillon, among the largest in France, we assessed the spatial dynamics of these habitats as well as their exploitation by local societies during the last three centuries. We found that despite having been expanding in the last decades, land-reclamations led to a massive reduction of their surface areas from 1705 to the 1970s. Moreover, if they were drained and mowed for a long time, these activities are more developed nowadays than in the 1950s. We finally revealed writings and archeological remains attesting for a salt-marsh hay storage and exportation since the beginning of the 18th Century. The result of such a history is that old and non-mowed patches are small and scattered among the current salt-marsh. Taking into account history and geography of coastal habitats allows us to identify the oldest and the last remaining patches of habitats that have been the least impacted by human activities. Such areas may represent a high conservation stake in the current context of massive land-cover and land-use changes in the littoral area.